Brain metastases from breast cancer - Santos, Joana (2020)
Background: Breast cancer (BC) is one of the commonest causes of brain metastases (BM): approximately 10-16 % of patients diagnosed with metastatic breast cancer will eventually develop BM during the course of their disease, however, certain subtypes have a higher risk of this event. The aim of this analysis was therefore to evaluate the prognosis and the pattern and imaging features of BM according to different BC subtypes.Patients and methods: We retrospectively reviewed the case records of patients with breast cancer and evidence of brain metastases from the database of IPO Porto between 2014-2018. The data obtained were statistically analysed.Results: We analysed 147 patients with BM from BC. The triple-negative subtype had the shortest overall survival (OS) after BM, besides a short period of time between BC and BM. HER2 overexpressing tumors had the longest OS. The estrogen-receptor positive group had the greatest interval between initial BC diagnosis and diagnosis of BM. Larger lesions showed a heterogeneous contrast enhancement and were heterogeneous pn T2WI sequences; a hyposignal on T2*WI was also associated with larger lesions. Triple-negative BC tended to have more heterogeneous lesions on T1WI. We noticed that the hippocampus is rarely affected by metastatic lesions.Conclusions: Based on the BC subtype it is possible to make a prediction about the prognosis of the disease and some imaging features of the BM, but not about their pattern of distribution. These data support further research concerning prevention, early detection, and treatment of BM from BC.